A finite-element approach for the analysis of pin-bearing failure of composite laminates (Fracture and Structural Integrity, 2014)
In this paper, a numerical home-made finite element model for the failure analysis of bolted joints between fiber-reinforced composite laminates is presented. The model is based on an incremental displacement basedapproach, it is hinged on the laminate theory and on a progressive material degradation governed by the failure of composite constituents. The model has been applied to a pin-plate system comprising a monodirectional fiber-reinforced laminated plate, and numerical results in terms of the bearing failure load have been successfully compared with available experimental data. Aim of this paper is to evaluate the effectiveness of Rotem’s and Huang’s failure criteria in predicting the pin-bearing failure of bolted joints. The selected criteria act at different material scale: the former operating at the laminate level, while the latter at the constituent’s scale. Proposed results seems to suggest that failure criteria accounting for micro-structural stress-strain localization mechanisms (for instance, Huang’s criterion) give a more accurate estimate in terms of pin-bearing failure load.
Keywords: Progressive damage